Experiences of Women Affected with Uterine Prolapse: A Qualitative Study from Baitadi District - Thagunna, RK; Yadav, DK; Yadav, RK (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Background: Women with uterine prolapse often suffer in silence as it negatively influences their physical, psychological as well as social well-being. This study aimed to explore the social and reproductive health problems associated with uterine prolapse. Methods: Using a purposive sampling, we conducted 16 in-depth interviews with uterine prolapse affected women in October 2016. Semi-structuredinterviews took place in women’s familiar environment i.e. the participant’s house in Baitadi district.Interviews were audio taped, transcribed and analyzed according to semantic and latent thematic analysis. Results:The theme describing the women’s experiencesregarding uterine prolapse was labeled as ‘experience of living with uterine prolapse’. The theme constitutes three categories: physical, psychological and social health. The category physical health constitutes five subcategories that represent how physical health of women was affected by uterine prolapse and their consequences: pain, discharge and itching, bleeding and dizziness, difficulty in walking, lifting and sitting, reduction in food intake. The category psychological health comprises three subcategories that define women’s feeling, thought and behaviour towards their prolapsed uterus: anxiety, stress and depressive feeling, fear of death, cancer and surgery. Conclusion: All physical, psychological and social aspects of women’s health are affected by uterine prolapse. Due to prolapse walking, sitting, working and lifting activities are become challenging for women. Women can become victims of violence due to their disability and less productivity. Uterine prolapse seriously compromises the sexual life of women affected.